THE VIOLATION OF LINGUISTIC POLITENESS PRINCIPLES WHICH DESCRIBES VERBAL BULLYING ON SOCIAL MEDIA IN THE MOVIE CYBERBULLY (2015) - Suharyati, Henny; Kristyowati, Dyah; Setiawan, Hasbia Lisdi (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
The research aims to identify the forms and types of behavior that reflect cyberbullying in the characters’ utterances in the Cyberbully movie and to analyze how many violations of politeness maxims are contained in the Cyberbully movie. The method used in this research is the qualitative method. The data in this research are the characters’ utterances that reflect cyber bullying which is collected using the listening and note-taking method. The results of this research are a violation of the tact maxim, a breach of the approbation maxim, and a violation of the sympathy maxim; types of cyberbullying behavior, denigration, and harassment; and several factors behind cyberbullying excitement and revenge.